2021
DOI: 10.1177/1759720x211024828
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal involvement and its association with the risk for nephritis in IgA vasculitis

Abstract: Background: We analysed clinical and biochemical parameters in predicting severe gastrointestinal (GI) manifestations in childhood IgA vasculitis (IgAV) and the risk of developing renal complications. Methods: A national multicentric retrospective study included children with IgAV reviewed in five Croatian University Centres for paediatric rheumatology in the period 2009–2019. Results: Out of 611 children, 281 (45.99%) had at least one GI manifestation, while 42 of 281 (14.95%) had the most severe GI manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
8
0
3
Order By: Relevance
“…Patients with HSP could have immune disorders outside the IgA compartment, and there could be interactions between IgA and other Igs, likely contributing to the higher likelihood of complications. 22 Furthermore, HSP in children with GI symptoms who had elevated neutrophil counts, B lymphocyte percentage, and reduced IgG levels were associated with refractory GI involvement. 6 Our study also demonstrated reduced IgG levels in HSP patients with GI bleeding than those without GI bleeding, indicating that humoral immune imbalance may contribute to HSP pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HSP could have immune disorders outside the IgA compartment, and there could be interactions between IgA and other Igs, likely contributing to the higher likelihood of complications. 22 Furthermore, HSP in children with GI symptoms who had elevated neutrophil counts, B lymphocyte percentage, and reduced IgG levels were associated with refractory GI involvement. 6 Our study also demonstrated reduced IgG levels in HSP patients with GI bleeding than those without GI bleeding, indicating that humoral immune imbalance may contribute to HSP pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…According to newer study the patients with IgAV started with gastrointestinal symptoms, older children with severe gastrointestinal symptoms (severe abdominal pain, intussusception, hematochezia and/or massive gastrointestinal bleeding) of IgAV were a particularly high-risk group for developing IgAVN. 33 In 10-20% of boys, orchitis may develop. Other rare manifestations include lung involvement, neurological manifestations and multiple organ involvement.…”
Section: Igavn and Other Clinical Manifestationsmentioning
confidence: 99%
“…It has not yet been defined whether the follow-up time should be extended for some groups of patients, ie, older children with the onset of gastrointestinal symptoms before other IgAV symptoms and severe GI form of IgAV, as well as those who develop ulcerations and necroses and persistent purpura, since they may be at higher risk for the later development of nephritis. 32,33 There are different suggestions for monitoring patients. According to one strategy, the initial urinalysis should be repeated three times.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…A meta-analysis from 2016 showed that gastrointestinal symptoms were strongly related to renal involvement (56), and several other studies have shown similar results (57)(58)(59). Patients in whom IgAV has started with gastrointestinal symptoms and older children with severe gastrointestinal symptoms (severe abdominal pain, intussusception, hematochezia, and/or massive gastrointestinal bleeding) may be a high-risk group for developing IgAVN (59). However, other studies have not confirmed this association (60)(61)(62).…”
Section: New Insights In the Clinical Presentations Of Igavmentioning
confidence: 99%
“…It is proposed to follow-up patients with IgAV for at least 6–12 months even if the initial blood pressure measurements and urinalysis are normal ( 74 ), measuring regularly blood pressure and performing urinalyses to detect presence of haematuria, and quantification of albuminuria and/or proteinuria. Bearing in mind that recently published research has indicated that a certain group of patients (such as older children with the onset of gastrointestinal symptoms before other IgAV symptoms and severe GI form of IgAV, as well as those who develop ulcerations and necroses and persistent purpura) may be at higher risk for the later development of nephritis, the question arises whether some children should be monitored longer than recommended ( 54 , 59 ).…”
Section: New Insights In the Follow-up Of Patients With Igavmentioning
confidence: 99%